Microwave‐Assisted Hydrothermal Synthesis of [Al(OH)(1, 4‐NDC)] Membranes with Superior Separation Performances. Issue 12 (8th May 2019) - Liu, Yi; Hori, Akihiro; Kusaka, Shinpei; Hosono, Nobuhiko; Li, Mingrun; Guo, Ang; Du, Dongying; Li, Yanshuo; Yang, Weishen; Ma, Yunsheng; Matsuda, Ryotaro
Abstract: In this study, we report a facile ligand‐assisted in situ hydrothermal approach for preparation of compact [Al(OH)(1, 4‐NDC)] (1, 4‐NDC=1, 4‐naphthalenedicarboxylate) MOF membranes on porous γ‐Al2 O3 substrates, which also served as the Al 3+ source of MOF membranes. Simultaneously, it was observed that the heating mode exerted significant influence on the final microstructure and separation performance of [Al(OH)(1, 4‐NDC)] membranes. Compared with the conventional hydrothermal method, the employment of microwave heating led to the formation of [Al(OH)(1, 4‐NDC)] membranes composed of closely packed nanorods with superior H2 /CH4 selectivity. Abstract : The power of microwave irradiation : [Al(OH)(1, 4‐napthalenedicarboxylate)] ([Al(OH)(1, 4‐NDC)]) MOF membranes were in situ hydrothermally grown on porous γ‐Al2 O3 substrates, which also served as the Al 3+ source. Microwave irradiation was found to exert significant influence on both microstructures and separation performances of prepared [Al(OH)(1, 4‐NDC)] membranes.